Persuasive imagery : a consumer response perspective - Scott, Linda M.; Batra, Rajeev (Advertising and consumer psychology., 2003)
Sponsored by the Society for Consumer Psychology, this volume synthesizes and advances existing knowledge of consumer response to visuals using an interdisciplinary perspective. It should be useful to those interested in consumer psychology, advertising, marketing and visual communication.